Theoretical investigation for Li2CuSb as multifunctional materials: Electrode for high capacity rechargeable batteries and novel materials for second harmonic generation - Ali Hussain, Reshak, Prof. Dr.; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr. (Elsevier B.V., 2011)
Link to publisher's homepage at http://www.elsevier.com/